A Novel Technique for Fabrication of Hollow Obturator for a Maxillary Defect: A Case Report - Sharma, P; Mathema, Suraj RB; Maskey, B (Journal of Nepalese Prosthodontic Society, 2022)
Prosthodontic rehabilitation following aggressive infections and malignancies is challenging. Surgical intervention may lead to anatomical defects resulting in oro-antral communication that causes difficulty in mastication, deglutition, impaired speech and facial disfigurement. The role of a Prosthodontist in maxillary defects is to restore these defects with the fabrication of obturators. However, the extent of the obturator into these large defects necessitate bulkier, heavy prosthesis which would likely be nonretentive and uncomfortable for the patient. Hollow bulb obturators are fabricated to reduce the weight of these prostheses. The method of fabrication of hollow bulb obturators with lost salt technique in the maxillary defect is described in this case report.